Psychological Responses to Progressive Exercise Until Voluntary Exhaustion: A Study of Adolescent Male Basketball Players. Issue 3 (June 2022) - Laki, Adam; Ihász, Ferenc; Szabo, Attila
The affective experience during and after exercise helps determine motivation, commitment, and adherence to sports. Choice reaction time (RT) is critical in decision-making and sports performance. In this within-subjects laboratory experiment, we scrutinized core affect and choice RT in 18 male adolescent basketball players during exercise sessions performed to voluntary exhaustion and during a control condition. The adolescents performed choice RT tasks in one of two exercise conditions and in the control session. Participants' feeling states differed between exercise and control sessions and decreased slightly even after moderate exercise intensity. Core affect also declined as the workload increased, but it remained pleasant-activated in all conditions. The RT errors increased at the peak exercise intensity. These results suggest that while high-intensity training might negatively affect young athletes' feeling states and impair their decision-making, their core affect remained positive, with large inter-individual variability. We discuss the practical implications of these results in adolescents' sports.